Soil nitrogen supply from effluent-amended pasture soils for forage maize production. Issue 2 (3rd April 2021) - Norris, Matthew; Johnstone, Paul R.; Wallace, Dirk F.; Arnold, Nathan P.; Parker, Mike
ABSTRACT: Field trials conducted in the Waikato region over three summer seasons (2007–08, 2008–09 and 2009–10) evaluated whether soil nitrogen (N) reserves at sites previously under long-term pasture and with a history of regular farm dairy effluent application were sufficient for maize production with either minimal or no additional N fertiliser inputs. Crop productivity was assessed in the first (six trials) and second (two trials) years following cultivation of pasture. In first year trials there were no productivity differences between no fertiliser control treatments (NF) and treatments receiving an application of starter fertiliser (SF) or starter and side dress fertiliser (SSF). In second year trials the SF treatment maximised yield at one site, but none was required at the other. Crop yields were high across all trials (22.9–31.9 t DM/ha). Results confirmed that in most cases there was adequate soil N to maximise crop productivity without the need for fertiliser inputs. Despite high crop N uptake, soil mineral N levels remained elevated (109–227 kg N/ha) at four sites after cropping, an observation attributed to high rates of mineralisation during the summer. There were few correlations between pre-plant soil tests and the amount of N mineralised at these sites.